THE RESISTIVITY MEASUREMENT OF DIPOLE-DIPOLE THE ARRAY TO IDENTIFY THE HORIZONTAL DEPOSIT AND VERTICAL CLIFT INFLUENCE (CASE STUDY at GOA JEPANG, BANDUNG) - (NIM : 22107021), WIDOWATI
The purpose of electrical surveys is to determine the subsurface resistivity distribution by making measurements on the ground surface. The vertical clift or rugged topography is one of parameter which cause the resistivity measurement result. The survey location was conducted at “Goa Jepang”, in Taman Hutan Rakyat Ir. H. Juanda, Bandung. The reason choice this “Goa Jepang” for the research is structure dimension of geology condition was known. The cave is anomaly looked of sill. Measurement done as much is 2 line, with “a” is 5,10 and 15 m, and “n” is 1,2,3,4,5 and 6. The first line is closed with vertical clift of ±8 metres and the second line have distance is ±23 metres from vertical clift. The result of resistivity interpretation surveys with dipole-dipole array by using Res2Dinv Program. The result from first line with “a” = 5,10,15 m and the second line with “a” = 15 m, the point out is the dimension model of cave at influence by vertical clift. Because depth penetration are even greater from line distance from vertical clift which is 8,35 m, 17 m and 25,5 m. influence of vertical clift to the effect current line that suppose make a half ball from homogoneus media will diffraction, so will regarded resistivity layered of all. Air has range resistivity is boundless to the effect resistivity this value increase cause ambiguinity or flase identification. Using the dipole dipole array, the cave was successfully detected. At line 2, for a spacing of 10 metres, the cave dimension was clearly detected because of the total length of dipole dipole array greater than the depth of penetration. This result could be applied to indicate sill deposits using the anomaly of resistivity value.